2015
DOI: 10.1088/1741-2560/12/6/066002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of evoked tactile sensation in forearm amputees with transcutaneous electrical nerve stimulation

Abstract: The stable PFM and sensory thresholds of ETS are desirable for a non-invasive neural interface that can feed back finger-specific tactile information from the prosthetic hand to forearm amputees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
101
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 71 publications
6
101
2
Order By: Relevance
“…Neuromuscular electrical stimulation (NMES) has been widely applied in clinical rehabilitation . Usually, electrical stimulation of motor fibers first excites the large‐diameter axons of motor units (MUs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuromuscular electrical stimulation (NMES) has been widely applied in clinical rehabilitation . Usually, electrical stimulation of motor fibers first excites the large‐diameter axons of motor units (MUs).…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation (NMES) has been widely applied in clinical rehabilitation. [1][2][3][4][5] Usually, electrical stimulation of motor fibers first excites the large-diameter axons of motor units (MUs). NMES also activates muscle contraction through a central mechanism by which motor units are recruited through spinal pathways by an evoked sensory volley.…”
Section: Introductionmentioning
confidence: 99%
“…However, differences in the perceived location of the feedback and the actual intended sensation can still limit the performance and increase response time [16,17]. When the feedback is also somatotopically matched, studies have shown promise in providing more intuitive sensory information, which reduces the cognitive load of the induced perceptions by evoking sensations in specific regions of the phantom hand or fingers [18][19][20][21][22][23]. Different somatotopic matching techniques range widely between non-invasive to invasive studies, each with their merits and costs.…”
Section: Introductionmentioning
confidence: 99%
“…With a flat interface nerve electrode, the common nerve trunk can be selectively recruited (Tyler and Durand, 2002). Recently, the transcutaneous electrical nerve stimulation (TENS) was applied to accomplish tactile sensation for the amputee (Chai et al, 2015) and healthy subjects (Forst et al, 2015). Due to the non-invasiveness, the TENS could be promising in wide clinical applications to elicit tactile feedback.…”
Section: Introductionmentioning
confidence: 99%